No-Tillage and High-Density Planting for Tahiti Acid Lime Grafted Onto Flying Dragon Trifoliate Orange - Azevedo, Fernando Alves de; Almeida, Rodrigo Fernandes de; Martinelli, Rodrigo; Próspero, Alexandre Gonçalves; Licerre, Raphael; Conceição, Patrícia Marluci da; Arantes, Ana Carolina Costa; Dovis, Verônica Lorena; Boaretto, Rodrigo Marceli; Mattos, Dirceu (Frontiers in Sustainable Food Systems, 2020)
The management of soil cover plants (intercropping) in orchards can contribute to increase productivity of citrus trees. Thus, the present research aimed to evaluate different planting systems for Tahiti acid lime grafted onto Flying Dragon trifoliate orange, a dwarfing rootstock, at high planting density (1,157 trees ha-1). The study was set up in four tillage systems, using Urochloa ruziziensis as an intercrop species in the orchard, and conducted for five years: no-tillage (NT), no-tillage and no-herbicide (NT-NH), minimum tillage (MT) and conventional tillage (CT; without intercropping). Dry matter (DM) production of biomass in the row and interrow of the orchard was evaluated yearly, as well as weed density, soil physical and chemical characteristics, plant water and nutritional status, and fruit yield of trees. Greater deposition of DM of biomass was observed in the row of citrus planting for treatments NT and NT-NH compared to CT and MT treatments, which led to reduced undesirable weed populations. The NT treatment also provided increases of 79% in potassium (K) nutrient concentrations in the leaves of trees and 60% in exchangeable K in the soil surface layer, in the first two years evaluated. The maintenance of the Urochloa ruziensis mulch in the NT system also provided higher soil volumetric moisture content and consequently lower soil resistance penetration and water stress on trees, evidenced by the predawn plant leaf water potential (<1 MPa). Moreover, the NT treatment provided an average increase of 56% of fruit yield from trees compared to the CT treatment during three harvests. This long-term study demonstrated the contribution of the no-tillage system using a favorable cover crop to increase the yield of Tahiti acid lime fruits and maintain the soil quality most required for the sustainability of citrus production. Citrus latifolia, ecological mower, intercropping, soil protetion, Urochloa ruziziensis, glyphosate management, yield.